Impact of self-service factors on customer value: How customer behavioral intentions are formed? - Hsiang-Ting Su (International Journal of Management, Economics and Social Sciences (IJMESS), 2021)
Service quality has been a topic of extensive inquiry for decades that has emerged in form of self-service which has profound effects on the way customers interact with firms to create positive service outcomes i.e., customer convenience, security, and behavioral intentions. This study focuses on investigating the factors that affect the consumer's intention to use self-service. This study also examines the mediating roles of customer value for the aforementioned relationships. An empirical survey research design was used to collect data from 350 customers using self-service in Taiwan. The data were analyzed using structural equation modeling approach to test the proposed hypotheses. The results showed the convenience, economy, security, and complexity factors are significantly related to customer value of self-service, despite of their different contribution. The study found mediating effect of customer value on the relationship between influencing context factors and behavioral intentions. These results provide insights for the service sector of the Taiwan to invest in self-service in order to enhance the consumer repurchase Intentions.
Keywords: L84; M31; 330; Service quality; self-service; behavioral intentions; customer value; Taiwan